Avaliação de aspectos imunomodulatórios induzidos por vesículas extracelulates (VEs) de pacientes com COVID-19 em células dendríticas derivadas de monócitos (mo-DC’s). - Laura do Amaral Xavier (2024)
Introduction: Extracellular vesicles (EVs) play an important role in intercellular communication due to their facilitated interaction with target cells, as well as the transport of various molecules, proteins, genetic material, and lipids originating from the parent cell, thus acting as cellular signaling mediators. In this study, the immunomodulatory potential of extracellular vesicles derived from the plasma of COVID-19 patients, Severe Acute Respiratory Syndrome (SARS) patients, and a control group was evaluated. Analyses were based on the phenotypic profile of monocyte-derived dendritic cells (mo-DCs) under the influence of these vesicles, as well as the functional evaluation of mo-DCs in activating T cells in a mixed leukocyte reaction (MLR). Materials and Methods: Plasma samples from COVID-19 patients (moderate or severe), SARS patients, and a control group were isolated using ultracentrifugation. Peripheral blood was collected from a healthy donor to obtain monocytes for in vitro differentiation into dendritic cells (mo-DCs) using IL-4 and GM-CSF cytokines (50ηg/ml) and adding EVs from COVID-19 patients (DC/EV COV), or EVs from SARS patients (DC/EV SARS), or EVs from the control group (DC/EV CTRL) for 5 days. For maturation of DC’s lipopolysaccharide (LPS) was added for 48 hours after differentiation. Phenotypic analysis of DCs was performed by flow cytometry evaluating the markers HLA- DR, CD80, CD86, CD11c, CD14, and PD-L1. The functional analysis of these DCs was conducted through an MLR with allogeneic T lymphocytes to assess the profile of induced adaptive immune response. Results: DC/EV COV showed decreased expression of HLA-DR and CD86 compared to DC/EV SARS and DC/EV CTRL. Additionally, we found higher levels of CD14 in DC/EV COV compared to DC/EV SARS, suggesting that EVs from COVID-19 patients promote an immature profile in mo-DCs. DC/EV COV cultured with allogeneic T lymphocytes induced an increase in regulatory T cell frequencies, as well as a decrease in IL-2 production by CD8+ T cells, an increase in PD-1 expression in CD8+ T cells, an increase in CTLA-4 expression in CD4+ and CD8+ T lymphocytes, suggesting a possible induction of peripheral tolerance. Moreover, CD4+ T lymphocytes co-cultured with DC/EV COV produced lower levels of INFγ and TNF. Conclusion: Based on the findings, it is concluded that EVs derived from moderate and severe COVID-19 patients are capable of using mechanisms to modulate the immune response to prevent the maturation of mo-DCs and the generation of effector responses mediated by CD4+ and CD8+ T cells. This mechanism was characteristic of SARS-CoV-2 infection associated with moderate and severe cases, considering the disparities in EV-induced responses related to other types of respiratory diseases with possible viral origin.